Teaching aid “What is Insurance?” / Nor Faizatul Azlia Amran ... [et al.] - Amran, Nor Faizatul Azlia; Mohamad Mokhtar, Aisyah; Othman, Nur Afini; Haji Sa’ari, Juan Rizal (Universiti Teknologi MARA, Kedah, 2023)
The teaching aid that we develop is expected to help people understand the importance of having insurance as an aspect of the preparation and protection towards any possibility that might happen. To attract the attention of our target audience and customers, we use simple illustrations and animations as an innovation. Our target audience does not understand insurance, which is a problem that led us to choose the aid tool as our innovation project. This is due to the fact that learning is limited and fails to grab their curiosity. Moreover, not being exposed to insurance and consequently not understanding the function of insurance is one of the issues we hope to solve through our project. The objectives of this teaching aid are to help people gain knowledge and enhance the ability of an individual to manage their healthy lifestyle and financial activities and thus contribute to the country's economic development. Next, we help them reduce risk in the future by taking insurance while being healthy so that if they are getting any chronic disease, they have insurance to cover their hospital bills. Hence, the uniqueness of our video is Animaker which is a versatile video making tool that helps produce high-quality animation for professional purposes. It enables students to visualize the complex of insurance. The benefits of our video can boost learner retention by simplifying interaction while our brains can interpret visual information rapidly. For the commercialization potential we have seen, our target market is people who seek to understand insurance such as university students. Plus, not every person has an idea what insurance is. So, we decided to help them to be more clear about insurance. We will do a cartoon story about insurance so that they can understand more easily.